The Phenomenon of Flexing Among Islamic Boarding School Students from an Islamic Economic Perspective: Between Consumerism and the Value of Simplicity in Islamic Boarding Schools - Sahro, Fatimatus; Sholikhah, Villatus (Li Falah: Journal of Islamic Economics and Business, 2026)
The rise of social media has brought about a transformation in people’s behavioral patterns and lifestyles, including within Islamic boarding schools, which are synonymous with the value of simplicity. This study aims to examine the phenomenon of “flexing” among students at the Nurul Imam Islamic Boarding School in Jember Regency from the perspective of Islamic economics. The research focuses on the forms of behavior emerging among students, the factors influencing the emergence of such behavior, the students’ efforts to uphold the value of simplicity amidst the tide of modern lifestyles, as well as the views of boarding school supervisors regarding the “flexing” phenomenon and strategies for instilling the value of simplicity in students. This study employs a qualitative approach using a case study design. Data collection techniques include observation, in-depth interviews, and documentation. Meanwhile, data analysis is conducted using the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions. The results indicate that the phenomenon of flexing among students is reflected through the use of branded goods, specific styles of appearance, and social media posts aimed at self-promotion and gaining social recognition. This phenomenon is influenced by the intensity of social media use, peer groups, the tide of modernization, and the growing culture of consumerism among youth. From an Islamic Economics perspective, flexing behavior has the potential to lead to attitudes of extravagance (israf), wastefulness (tabdzir), and ostentation (riya') if practiced excessively. Nevertheless, some boarding school students still strive to uphold the value of simplicity through self-control, limiting consumptive behavior, and adopting a selective attitude toward emerging trends. This study concludes that the phenomenon of flexing represents an interaction between modern culture and the values of simplicity in Islamic boarding schools, thus requiring the reinforcement of Islamic economic values in addressing social dynamics in the digital age.